A Radiomics Model Based on Gd-EOB-DTPA-Enhanced MRI for the Prediction of Microvascular Invasion in Solitary Hepatocellular Carcinoma ≤ 5 cm - Qu, Chengming; Wang, Qiang; Li, Changfeng; Xie, Qiao; Cai, Ping; Yan, Xiaochu; Sparrelid, Ernesto; Zhang, Leida; Ma, Kuansheng; Brismar, Torkel B. (Frontiers in Oncology, 2022)
Aims: To establish and validate a radiomics-based model using preoperative Gd-EOB-DTPA enhanced MRI to predict microvascular invasion (MVI) in patients with hepatocellular carcinoma ≤ 5 cm. Methods: Clinicopathologic and MRI data of 178 patients with solitary HCC (≤ 5 cm) were retrospectively collected from a single medical center between May 2017 and November 2020. Patients were randomly assigned into training and test subsets by a ratio of 7:3. Imaging features were extracted from the segmented tumor volume of interest with 1 cm expansion on arterial phase (AP) and hepatobiliary phase (HBP) images. Different models based on the significant clinical risk factors and/or selected imaging features were established and the predictive performance of the models was evaluated. Results: Three radiomics models, AP_model, HBP_model and AP+HBP_model were constructed for MVI prediction. Among them, the AP+HBP_model outperformed the other two. When it was combined with a clinical model, consisting of tumor size and alpha-fetoprotein (AFP), the combined model (AP+HBP+Clin_model) showed an area under the curve of 0.90 and 0.70 in the training and test subsets, respectively. Its sensitivity and specificity were 0.91 and 0.76 in the training subset and 0.60 and 0.79 in the test subset, respectively. The calibration curve illustrated that the combined model possessed a good agreement between the predicted and the actual probabilities. Conclusions: The radiomics-based model combining imaging features from arterial and hepatobiliary phases of Gd-EOB-DTPA enhanced MRI and clinical risk factors provides an effective and reliable tool for preoperative prediction of MVI in patients with HCC ≤ 5 cm.